Comparative impact of partial replacement of soybean meal with select specialty protein ingredients in broiler chicken starter feeding program on growth, organ, intestinal, plasma, and litter attributes to 49 days of age - Anastasia K. Tsementzis; Anderson N. Maina; Colin A. De Cloet; David Trott; Lee-Anne Huber; Marie-Pierre Létourneau-Montminy; Elijah G. Kiarie (Poultry Science, 2025)
Speciality protein ingredients (SPI) are often added to partially replace regular soybean meal (SBM) in starter phase to bolster growth. However, there is limited comparative data on the effectiveness of this approach on lifetime growth performance in broiler chickens. We assessed the impact of inclusion of select SPI in the starter phase (0 to 10 days of age) and subsequent impact on growth, organ, intestinal, plasma, and litter attributes up to 49 days of age. Five iso-caloric and -nitrogenous starter diets were formulated to meet or exceed specifications: 1) Negative Control (NC), corn and SBM-based, 2) ETSBM, NC+15.5% enzymatically treated SBM, 3) SPC, NC+ 9.9% soy protein concentrate, 4) PM, NC+ 11.3% pork meal and 5) BSFLM, NC+ 13.0% black soldier fly larvae meal. A sixth diet (PC) was formulated by adding antibiotic growth promoters (AGP) in NC as positive control. Day old male Ross 708 chicks were placed in 48 floor pens (35 birds/pen), fed test diets for 10 days and transitioned to common grower and finisher diets. The BW and feed intake were monitored by phase. Birds were sampled on d 10 and 28 for plasma, organ weight, and digesta. Litter samples were taken from d 46 to 48. On d 10, PC, and SPI birds were heavier (P<0.001) than NC birds. Overall (d 0-49), birds fed PC had similar d 49 BW to birds fed SPI diets but higher (P≤0.02) than birds fed NC. Overall, birds fed PC and PM ate more (P=0.024) feed than NC birds, however, there were no (P=0.107) diet effects on FCR. In conclusion, partial replacement of SBM with SPI was commensurate to AGP in bolstering growth in starter phase resulting in heavier birds at market. There were few differences across treatments regarding plasma, intestinal and litter attributes indicating that the effects of the incorporation of SPI were limited to growth performance.